Weed control efficacy and winter wheat response to saflufenacil - Frihauf, John Carl (Kansas State University, 2009)
Saflufenacil is an experimental herbicide for control of broadleaf weeds in various crops including several herbicide resistant weed biotypes. Wheat is highly tolerant to preplant and preemergence applications of saflufenacil, but winter wheat growers prefer to apply herbicides postemergence (POST) in early spring. Objectives of this research were to (1) evaluate winter wheat and four common broadleaf weed species response to POST treatments of saflufenacil applied alone and in combination with bentazon or auxin herbicides at various rates both with and without adjuvants, and to (2) determine the possible mechanism(s) responsible for crop safening observed when saflufenacil is applied with 2,4-D amine or bentazon in winter wheat. Growth chamber, greenhouse, and field studies showed saflufenacil at a minimum rate of 25 g/ha controlled blue mustard and flixweed >85% when saflufenacil was applied alone or mixed with dicamba, 2,4-D amine, 2,4-D ester, or MCPA ester. Also, mixtures of bentazon with 13 g/ha of saflufenacil resulted in death of kochia, but increasingly higher rates of 2,4-D amine were needed to achieve 90% growth reduction when saflufenacil rates were decreased from 50 to 25 to 13 g/ha. In general, most of the saflufenacil combinations tested controlled henbit <85%. Leaf necrosis and stunting of winter wheat were reduced by tank mixing saflufenacil with dicamba, 2,4-D amine, or bentazon, but not with MCPA ester or 2,4-D ester. Including nonionic surfactant (NIS) in mixtures of saflufenacil plus 2,4-D amine resulted in significant wheat injury similar or greater than injury caused by saflufenacil plus NIS. Finally, 2,4-D amine enhanced saflufenacil absorption into winter wheat plants, whereas bentazon reduced absorption of saflufenacil. No more than 11% of applied saflufenacil translocated out of treated leaves to other plant parts when applied alone or when saflufenacil was mixed with 2,4-D amine or bentazon. Metabolism of saflufenacil by wheat plants was not affected by tank mixing with bentazon, but saflufenacil metabolism was slowed by mixing with 2,4-D amine. Overall, these studies indicate saflufenacil can potentially be used POST in wheat at an optimum rate of 25 g/ha plus 2,4-D amine or dicamba to effectively control blue mustard and flixweed.
Keywords: saflufenacil; BAS 800H; winter wheat; winter annual weeds; crop response; absorption; Agriculture, Agronomy (0285)